1980
DOI: 10.1246/cl.1980.743
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ring Closure Reaction Between 1,4-Dihydroxyanthraquinone and Ethylenediamine Promoted by Copper Ions

Abstract: The reaction of 1,4-dihydroxyanthraquinone with ethylenediamine in the presence of Cu(I)Cl or Cu(II)Cl2 gave 6-hydroxy-1,2,3,4-tetrahydronaphtho- (2, 3-f) -quinoxaline- 7,12-dione in quantitative yield at ambient temperature. The reaction was promoted greatly by copper ions. The possible mechanism and the role of copper ions were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Matsuoka and colleagues observed that a large excess of butylamine reacts with 5,8-dihydroxy-1,4-naphthoquinone in the presence of 2 mol equivalents of copper(II) salts to give a variety of products resulting from both nucleophilic substitution of the hydroxyl groups and oxidative coupling, whereas the analogous reaction with 1,4-dihydroxyanthraquinone selectively gave 2-butylamino-1,4-dihydroxyanthraquinone . A similar reaction with ethylenediamine gave a product resulting from oxidative addition and cyclization . Yoshida and co-workers found that N -alkylanilines regioselectively react at the 6-position with quinolin-5,8-dione in the presence of a molar equivalent of copper(II) acetate to give mixtures of products resulting from oxidative coupling to both the para position and the nitrogen of the aniline derivative .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsuoka and colleagues observed that a large excess of butylamine reacts with 5,8-dihydroxy-1,4-naphthoquinone in the presence of 2 mol equivalents of copper(II) salts to give a variety of products resulting from both nucleophilic substitution of the hydroxyl groups and oxidative coupling, whereas the analogous reaction with 1,4-dihydroxyanthraquinone selectively gave 2-butylamino-1,4-dihydroxyanthraquinone . A similar reaction with ethylenediamine gave a product resulting from oxidative addition and cyclization . Yoshida and co-workers found that N -alkylanilines regioselectively react at the 6-position with quinolin-5,8-dione in the presence of a molar equivalent of copper(II) acetate to give mixtures of products resulting from oxidative coupling to both the para position and the nitrogen of the aniline derivative .…”
Section: Resultsmentioning
confidence: 99%
“…40 A similar reaction with ethylenediamine gave a product resulting from oxidative addition and cyclization. 41 Yoshida and co-workers found that N-alkylanilines regioselectively react at the 6-position with quinolin-5,8-dione in the presence of a molar equivalent of copper(II) acetate to give mixtures of products resulting from oxidative coupling to both the para position and the nitrogen of the aniline derivative. and co-workers as part of their synthetic studies on the preparation of isoquinolindiones reported the oxidative coupling of amines with 5-isoquinolinol to give 8-dialkylamino-5,6-isoquinolinediones and the 7-isoquinolinol to give 3,5-(dialkylamino)-7,8-isoquinolinediones in the presence of 50 mol % copper(II) acetate.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…Optimum reaction temperature was 50 °C, as lower temperature led to a slow reaction. High temperature led to the following reaction shown in Scheme 3 [13]:…”
Section: Synthesis Of Blue Crosslinking Dyementioning
confidence: 99%
“…Leuco-quinizarin, characterized by its highly active diketone skeleton, serves as a versatile reactant capable of functioning as both an electrophile and a nucleophile. Its efficient conversion into a wide range of compounds has been recognized since Marschalk’s discovery in 1936. ,,,,,,,, Several methodologies for the synthesis of leuco-quinizarin from quinizarin, a readily available and cost-effective substrate, involve the use of stoichiometric amounts of inorganic reductants and bases or acids, such as sodium hydrosulfite (dithionite) bases, ,,,,,,,,,,,, Al(0) or Zn(0) acids, CuCl 2 acids, Fe 2+ acids, and SnCl 2 acids in most cases (Figure a). Although these synthetic methods have been widely used, large amounts of waste or toxic gas from stoichiometric reductants are generated; moreover, neutralization is required during the workup process.…”
mentioning
confidence: 99%